A cselgáncs versenyképessége Magyarországon - Madarász, Tamás; Kucsma, Daniella (Acta Scientiarum Socialium, 2015)
The Competitiveness of Judo in Hungary. The objectives of the Hungarian Judo Association are well defined, realistic, and can contribute to improving the competitiveness of the sport. The judo is one of the few Olympic sports that do not have a separate sports hall, so the rents are a continuous problem to be solved. Regarding the success rate there is a steady progress; selected athletes in every age group win more and more medals and top prizes. Success, of course, helps developing the recruitment base of the sport. The present 191 sections of the Hungarian Judo Association (HJA) do not cover all the 174 districts of Hungary outside Budapest. There is a strong intent to correct it in the coming years. HJA is also committed to promote the athletes’ successful civilian life after their sports career. Another featured goal of the sport’s national management team is to preserve the good professional relationships with the other Olympic sports branches as well as with those non-Olympic sports branches that also belong to the family of martial arts. A good proof of this is the fact that judo is used as an additional sport to many other branches of sport such as football and basketball in youth sports education, with present plans to extend it to several more branches as well. The publication was supported by the SROP-4.2.2.B-15/1/KONV-2015-0001 project. The project has been supported by the European Union, co-financed by the European Social Fund.